Penggunaan Media Interaktif Berbasis Wordwall Game untuk Meningkatkan Partisipasi Belajar Siswa pada Mata Pelajaran PPKn di SMP - Jumahir Jumahir; Zedi Muttaqin; Nurul Wahidah; Nurul Miiraz; Irwan Saputra; Munawir Haris; Sri Nirwana (Universitas Muhammadiyah Mataram, 2026)
Abstract: Learning participation is one of the important factors in determining learning success; however, students' participation in Civics Education learning remains relatively low. Low participation is reflected in students' lack of confidence in asking and answering questions, participating in discussions, expressing opinions, and paying attention during the learning process. Therefore, innovative learning media are needed to create more interactive and engaging learning experiences. This study aimed to improve students' learning participation through the use of interactive Wordwall Game-based media in Civics Education learning at SMPN 2 Labuapi. The novelty of this study lies in the implementation of gamification-based Wordwall Game media to enhance students' learning participation in junior high school Civics Education by measuring six participation indicators, namely asking questions, answering questions, participating in discussions, paying attention to teacher explanations, expressing opinions, and actively using Wordwall during learning activities. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages conducted in two cycles. The research subjects were 32 eighth-grade students of SMPN 2 Labuapi. Data were collected through observation, questionnaires, and documentation. The data were analyzed descriptively using qualitative and quantitative approaches with percentage analysis. The results revealed that the average students' learning participation increased from 33.3% in the pre-cycle stage to 65.6% in Cycle I and further increased to 87.5% in Cycle II. These findings indicate that the use of interactive Wordwall Game-based media effectively improves students' learning participation by creating a more interactive, enjoyable, and student-centered learning environment. Therefore, Wordwall Game can serve as an innovative instructional medium to enhance students' participation in Civics Education learning.Abstrak: Partisipasi belajar merupakan salah satu faktor penting dalam menentukan keberhasilan pembelajaran, namun pada praktiknya partisipasi siswa dalam pembelajaran PPKn masih tergolong rendah. Rendahnya partisipasi ditunjukkan oleh kurangnya keberanian siswa dalam bertanya, menjawab pertanyaan, berdiskusi, menyampaikan pendapat, serta kurangnya perhatian siswa selama pembelajaran berlangsung. Oleh karena itu, diperlukan media pembelajaran yang mampu menciptakan pembelajaran yang lebih interaktif dan menarik. Penelitian ini bertujuan untuk meningkatkan partisipasi belajar siswa melalui penggunaan media interaktif berbasis Wordwall Game pada mata pelajaran PPKn di SMPN 2 Labuapi. Kebaruan penelitian ini terletak pada penerapan media Wordwall Game berbasis gamifikasi untuk meningkatkan partisipasi belajar siswa pada mata pelajaran PPKn di jenjang SMP dengan mengukur enam indikator partisipasi belajar, yaitu aktif bertanya, menjawab pertanyaan, aktif berdiskusi, memperhatikan penjelasan guru, menyampaikan pendapat, dan aktif menggunakan media Wordwall selama pembelajaran. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus dengan tahapan perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian berjumlah 32 siswa kelas VIII SMPN 2 Labuapi. Teknik pengumpulan data menggunakan observasi, angket, dan dokumentasi. Data dianalisis secara deskriptif kualitatif dan kuantitatif menggunakan persentase. Hasil penelitian menunjukkan bahwa rata-rata partisipasi belajar siswa meningkat dari 33,3% pada tahap pra-siklus menjadi 65,6% pada siklus I dan meningkat menjadi 87,5% pada siklus II. Hasil tersebut menunjukkan bahwa penggunaan media interaktif berbasis Wordwall Game efektif dalam meningkatkan partisipasi belajar siswa karena mampu menciptakan pembelajaran yang lebih interaktif, menyenangkan, dan berpusat pada siswa. Dengan demikian, media Wordwall Game dapat dijadikan sebagai alternatif media pembelajaran inovatif untuk meningkatkan partisipasi belajar siswa pada mata pelajaran PPKn.